PERAN ACCOUNT PAYABLE DALAM MENERAPKAN SOP PAYMENT DI INDUSTRI PERHOTELAN - Rumiris; Ekadjaja, Margarita (Jurnal Serina Abdimas, 2024)
The partner in this community service activity are hotels in the Jakarta Barat` areas. Partner leaders really pay attention to and maintain relationships with customers and suppliers, but considering the lack of administrative workers in managing payable accounts, partners are willing to collaborate with FEB UNTAR by providing opportunities for FEB UNTAR management students to do internships in the hotel industry. The method for implementing internship activities is carried out offline for six months. The schedule for implementing internship activities is from Monday to Friday, starting from nine in the morning to six in the afternoon. One of the activities carried out is studying accounts payable from the purchasing aspect in receiving goods and invoices, supporting documents in payment procedures to suppliers, and the important role of Accounts Payable in the finance department. The results obtained by the partners were very satisfied with the intern students' persistence in checking data related to the smooth running of activities in the accounts payable department. Apart from earning additional income, intern students also get additional information about the importance of the role of accounts payable in handling accounts payable to ensure smooth company cash flow. The Accounts Payable Department needs to implement procedures for orderliness and completeness of documents before checking by senior accountants, verifying documents, recording data and market list documents, as well as making payments Mitra pada kegiatan abdimas ini adalah hotel di wilayah Jakarta Barat. Pimpinan mitra sangat memperhatikan dan menjaga hubungan dengan customer dan supplier namun mengingat kurangnya tenaga kerja administrasi dalam mengelola account payable maka mitra bersedia bekerja sama dengan FEB UNTAR dengan memberikan kesempatan kepada mahasiswa jurusan manajemen FEB UNTAR untuk magang di industri perhotelan,. Metode pelaksanaan kegiatan magang dilakukan secara luring selama enam bulan. Jadwal pelaksanaan kegiatan magang dilakukan dari hari Senin hingga Jumat yang dimulai dari  pukul sembilan pagi hingga pukul enam sore. Salah satu kegiatan yang dilakukan adalah mempelajari hutang dagang dari aspek purchasing dalam penerimaan barang dan invoice, dokumen pendukung dalam prosedur payment kepada supplier, dan peran penting Account Payable dalam departemen finance. Hasil yang diperoleh mitra sangat puas dengan ketekunan mahasiswa magang dalam mengecek data-data terkait dengan kelancaran kegiatan di departemen account payable. Selain memperoleh income tambahan, mahasiswa magang juga memperoleh tambahan informasi mengenai pentingnya peran account payable dalam penanganan hutang dagang guna kelancaran arus kas perusahaan. Departemen Account payable perlu menerapkan prosedur dalam ketertiban dan kelengkapan dokumen sebelum pengecekan oleh senior accountant, memverifikasi dokumen, mencatat data dan dokumen market list, serta dalam melakukan pembayaran.